The empirical properties of some popular estimators of long memory processes - Rea, W.; Oxley, Leslie; Reale, M.; Brown, J. (2011)
The empirical properties of 12 different estimators of the Hurst parameter, H, or fractional integration parameter, d, derived via simulation, are presented. For time series with fewer than 4,000 observations only the Whittle and Haslett-Raftery estimators produce acceptable statistical properties.